2010
DOI: 10.1002/jctb.2551
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrochemical systems for efficient recalcitrant wastes treatment

Abstract: Recalcitrant wastes including dyes, pesticides, explosives, heavy metals, polyalcohols, furan derivatives and phenolic substances, are of special concern owing to their recalcitrance and persistence in the environment. Bioelectrochemical systems (BESs) including microbial fuel cells (MFCs) and microbial electrolysis cells (MECs), integrate three important wastewater treatment options, namely, biological treatment, electrolytic dissociation and electrochemical oxidation/reduction, and are regarded as a new sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(64 citation statements)
references
References 97 publications
1
63
0
Order By: Relevance
“…An up-to-date review is provided on recent research and development in BESs-based recalcitrant wastes treatment [44]. Recently, the reduction of perchlorate in the cathode compartment of a BES has been described [45].…”
Section: Clomentioning
confidence: 99%
“…An up-to-date review is provided on recent research and development in BESs-based recalcitrant wastes treatment [44]. Recently, the reduction of perchlorate in the cathode compartment of a BES has been described [45].…”
Section: Clomentioning
confidence: 99%
“…This emerging cathodic reduction technology has great potential utilization in the wastewater treatment with the features of higher efficiency and selectivity of the reduction process (cathode providing continuous electrons), environmental friendliness (adding no chemicals and applying tiny voltage) and low-cost (without expensive catalyst) (Huang et al, 2011;Zhang and Angelidaki, 2014). Previous studies have showed that antibiotics CAP could be efficiently reduced to antibacterial inactivity products by cathode.…”
Section: Introductionmentioning
confidence: 99%
“…The toxic effect of Cu 2 + in activated sludge was shown in weak acid and alkaline conditions. When pH was above 7.5, Cu 2+ could transfer into Cu(OH) 2 and decrease the toxicity. However, the dissolved Cu 2+ can also cause the irreversible protein denaturation, which will affect the biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment method of coking wastewater treatment in the world is the biochemical treatment process of aerobic activated sludge. In recent years, with the environmental protection agency on the water safety calls for more and more intense, many manufacturers began to proceed in activated sludge process for coking wastewater treatment process of the subsequent section increased ozone oxidation and activated carbon adsorption and other high technology content depth processing technology, the treatment of wastewater in the chroma and chemical oxygen demand (COD) to have obvious improvement [2].…”
Section: Introductionmentioning
confidence: 99%